Pelaksanaan Digitalisasi Peradilan Dalam Gugatan Perdata di Pengadilan Negeri Purbalingga - Setia Putri, Nasrullah Alfalaq (UMPurwokerto Law Review, 2024)
Abstract Digitalization is currently penetrating into all aspects of life, including in the process of the judicial system in the District Court. The Supreme Court through Supreme Court Regulation (PERMA) Number 1 of 2019 concerning Case Administration and Trial in Court Electronically which replaces PERMA Number 3 of 2018 concerning Case Administration in Court Electronically, issued an E-Court system or electronic case administration. However, in practice at the Purbalingga District Court there are still obstacles experienced in the process of digitizing this court. The purpose of this study is to determine and analyze the implementation and obstacles of judicial digitization in civil lawsuits at the Purbalingga District Court. The method used in this research is normative juridical method. The data collection method used to collect secondary data in this research is library research. The result of the research shows that the implementation of digitization in the District Court there are obstacles experienced in the form of internal factors, namely the existence of limited human resources in the form of clerks as e-court administrators, minimal e-court desk services, IT facilities and infrastructure and lack of budget as well as its mandatory nature, but requires approval from the plaintiff and defendant, relatively closed proceedings because access is only owned by both parties. and not for the public and the evidentiary process that is not maximized and externally in the form of human resources of the parties or e-court service users who litigate. Keywords: digitalization, e-court, constraints Abstrak Digitalisasi saat ini merambah ke segala sendi kehidupan termasuk dalam proses sistem peradilan di Pengadilan Negeri. Mahkamah Agung melalui Peraturan Mahkamah Agung (PERMA) Nomor 1 Tahun 2019 tentang Administrasi Perkara dan Persidangan di Pengadilan secara Elektronik yang menggantikan PERMA Nomor 3 Tahun 2018 tentang Administrasi Perkara di Pengadilan secara Elektronik, mengeluarkan sistem E-Court atau administrasi perkara secara elektronik. Namun dalam praktiknya pada Pengadilan Negeri Purbalingga masih terdapat kendala-kendala yang dialami dalam proses digitalisasi perdilan ini. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis pelaksanaan serta kendala digitalisasi peradilan dalam gugatan perdata di Pengadilan Negeri Purbalingga. Metode yang digunakan dalam penelitian ini adalah metode yuridis normatif. Metode pengumpulan data yang digunakan untuk mengumpulkan data sekunder dalam penelitian ini ialah studi kepustakaan (library research). Hasil penelitian menunjukkan pelaksanaan digitalisasi di Pengadilan Negeri terdapat kendala yang dialami berupa faktor internal yaitu adanya keterbatasan SDM berupa panitera sebagai administrator e-court, pelayanan meja e-court yang minim, sarana dan prasarana IT dan kurangnya anggaran serta sifatnya yang mandatory, melainkan memerlukan persetujuan dari penggugat dan tergugat, perisadangan relatif tertutup karena akses hanya dimiliki oleh kedua belah pihak dan tidak untuk umum dan proses pembuktian yang tidak maksimal dan eksternal yaitu berupa SDM para pihak atau pengguna jasa pelayanan e-court yang berperkara. Kata kunci: digitalisasi, e-court, kendala